ANALYSIS OF MICROGRAPH OF ACTIVATED ADSORBENTS - Jumaeva, Dilnoza; Raximov , Umidjon; Muxtorjonov , Muxammadali (Educational Research in Universal Sciences, 2023)
In this article, research was conducted on the methods of obtaining adsorbents, using the problem of waste generated in the process of the juice production enterprise as a solution to its economic problems. In the results of scanning electron microscope image analysis of adsorbent samples activated thermally and with water vapor at temperatures of 700°С, 800°С in the presence of waste extracted from grape seed juice, the results of the spectra of the distribution of elements with the morphology of adsorbents on the surface of the sample are presented.